Geographic Distribution Of Protected Sedge Species Carex Pilosa Scop. In Latvia With Reference To Forest Ecosystems (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The results of field studies, laboratory research and desk-based GIS geospatial analysis of ecological factors which determine geographic distribution of hairy sedge (Carex Pilosa Scop.) in Latvia with reference to forest ecosystems are presented in this article. Hitherto such a complex studying of chorology and ecology of this protected forest herb has not been performed before in Latvia, nor has it been attempted in the other Baltic states. The obtained results demonstrate that this protected plant species ecologically is quite plastic regarding its growing conditions and can be found in different forest ecosystems, however the most vital and largest cenopopulations of Carex pilosa are associated with the old deciduous forests, particularly those growing within erosion landforms on the slopes of the southern or south-eastern aspect. This research is important both from the scientific and practical view point, allowing to work out recommendations for the protection and conservation of this rare species in Latvia.